Kebijakan Perlindungan Data Pribadi Dalam Menanggulangi Kejahatan Lintas Negara di Era Ekonomi Digital - Nilam Cahya Fajria; Andi Aina Ilmih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Digital Economy Era as a driver of economic growth in Indonesia has penetrated almost all aspects of life. The rapid development of the digital economy has the potential to create risks and challenges in the future. The widespread use of digital technology in electronic transactions has made information no longer limited as a medium for transactions and communication, but rather a source of profit in the economy. Personal data information is not always used correctly, and can even be misused by irresponsible parties. Facing this, the importance of protecting personal data in electronic transactions, by strengthening a digital- based security system to mitigate the risk of crime in the digital economy era.